Interest and willingness to pay for investigative reporting: a solution for the crisis of journalism? (Communication & Society, 2016)
The Internet has stimulated a cross-shift in the business model across the media sector. Traditional funding sources have been reduced by the voracious pulse for free access and nonprofessional actors have swarmed over to compete with traditional channels of information. This paper attempts to analyze willingness-to-pay for investigative journalism contents from a general audience’s point of view, in order to find consumption patterns that could orientate professionals in this crisis. To achieve such an aim, a survey was conducted to examine the paying habits of Madrid’s population using a multistage technique, which was designed following the indexes provided by the Municipal Register of the town. The results, based on three payment channels –micro-payment, donation and annual subscription– and three distribution channels – corporate media, non-corporate media and freelance journalists– confirm the interest of the audience for investigative reporting findings but also their unwillingness to pay for its scoops or exposés.